Development of a multimedia training course for user self-development - Khoroshevska, Iryna; Khoroshevskyi, Oleksii; Hrabovskyi, Yevhen; Lukyanova, Viktoriia; Zhytlova, Iryna (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the composition, content, and features of analytical and applied tasks that must be solved in the process of creating a multimedia training course for user self-development. In the context of this work, the problem of the lack of a clear definition of the content-element composition of analytical and applied tasks, which must be solved during the creation of such a course, was solved. An analysis of research into various aspects of the creation of multimedia publications, complexes, courses for self-education and self-development of users in various fields is provided. The systematization and determination of the content and features of analytical and applied tasks were carried out, which should be resolved during the development of the course. Keyword research is based on the analysis of user searches. As a result, "succulent species" (1–10k/month) and "breeding succulents" (100–1k/month) were added as course topics. In order to identify positive practices and bring them to the course, the functionality of analogs was investigated. The development of the technical task makes it possible to determine the elemental and content composition, structural and technological aspects of the course. The choice of the most appropriate software environment for the development of a multimedia educational course was substantiated (through the prism of the analysis of the functionality required for this purpose). An appropriate stylistic direction for the implementation of the design of the course interface has been determined. Page prototypes were created. The implementation of the course and its interactive components (advice, exercises, tests, games) was carried out in the selected Adobe Captivate environment. The solution of each task is illustrated by an example. To demonstrate the creation of a multimedia course, self-development of the user in matters of caring for succulents was chosen. The developed publication is used in the educational discipline "Technologies of electronic publishing" as an illustrative example of creating a course.